TANGGUNG JAWAB HUKUM BIRO PERJALANAN UMRAH TERHADAP CALON JAMAAHNYA - Jeremi Korayan; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2018)
As a legal subject, Umroh organizing agency has the legal responsibility of Umroh congregation, responsibilities relating to the concept of legal obligations. A person is legally responsible for a particular act or that he or she assumes legal liability means that he or she is responsible for a sanction in the event of a conflicting action. From legal aspect, Umroh organizing agency's legal responsibility can be seen from civil, criminal, and administrative aspects. Many of the Umroh organizing agency although it has permission from the government but in its implementation is not in accordance with the provisions set forth in the legislation regulating the implementation of Hajj and Umroh. This can result in losses for pilgrims who use the umroh organizing agency. For example, in practice, many Umroh organizing angency do not give written agreements. The agreement is usually done with a verbal agreement promising. Therefore, when the rights and obligations of the parties is not met, there is no authentic evidence to prosecute and no limits on liability. Actually, a written contract is regulated and stipulated in Article 45 of Law. 13/2008 on Organizing Haj Pilgrimage to Mecca. Thus the form of agreement of appointment of departure between the Umroh organizers agency with prospective pilgrims so that umroh can be known various responsibilities of the umroh organizers agency in case of incompatibility between the agreement with the realization.